The Effect of Paired Storytelling Learning Model on Speaking Skills of Grade 4th Elementary School Students - Firsdiva, Neisca Paramitha; Rini, Titis Angga; Arafik, Muh (Universitas Negeri Malang, 2024)
This research uses a quantitative experimental approach and uses a type of pre-experimental research with a one group pre-test and post-test design. The aims of this research are (1) to determine the speaking skills of grade 4 students at SDN Karangbesuki 3 Malang before and after being given treatment, and (2) to determine whether or not there is an effect of using the paired storytelling learning model on the speaking skills of grade 4 students in SDN Karangbesuki 3 Malang. The independent variable in this research is the paired storytelling learning model while the dependent variable is the speaking skills of class 4 students at SDN Karangbesuki 3 Malang, totaling 30 students. In this research, to determine the sample using Nonprobability Sampling with a type of sampling technique, namely Saturation Sampling. Data was collected from the pre-test, treatment and post-test divisions then analyzed descriptively and inferential statistical analysis using parametric statistical tests, namely the independent sample t-test using JASP software. The results of this research show that: the implementation of the learning process using the paired storytelling learning model on students' speaking skills is in the effective category, the students' speaking skills before and after implementing the paired storytelling learning model have increased, after carrying out hypothesis testing and analysis, the results obtained are: significant influence of the application of the paired storytelling learning model on students' speaking skills. The conclusion in this research is that the paired storytelling learning model influences the speaking skills of grade 4 students at SDN Karangbesuki 3 Malang. Keywords: Paired storytelling, speaking skills, elementary school students